Studi Ekologis Dalam Perencanaan Rumah Tinggal Di Nganjuk - Juwito, Juwito; Junianto, Junianto; Winansih, Erna (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2018)
To accommodate the daily activities of a small family, efforts are needed to present are presentative residence. harmony with nature, humans, and the built-in environment, sustainably and sustainably is the Start Point. The ‘Ecological Architecture’ approach in planning the Residence in Nganjuk is chosen as the guiding line. The basic thing is whether there is an alignment between the architectural concept and the end result of his work. This research methodology uses descriptive and literature studies. this research attempts to analyze the design work with the concept of ecological architecture, based on the theory of ecological architecture from (Heinz Frick., 2006). The results of this study indicate that this Residence is a small example of the application of ‘Ecological Architecture’.The parameters can be seen from Adjusting design work to the environment, maintaining environmental resources, saving natural energy sources, utilizing natural resources around the area for building systems, both related to building materials and for building utilities. Implement 4R (reduce, reuse, recycle, repair) on the material used. the type of material that can be returned to nature in accordance with the cycle. with a building orientation pattern (east-west) to dominant vista facing north-south to become the center of sensing into the interior layout along with the parks and water spots. DOI: https://doi.org/10.26905/lw.v10i2.2683